STRATEGI PENGELOLAAN SAMPAH MELALUI SOSIALISASI INISIASI BANK SAMPAH DI KELURAHAN RAWA MAKMUR PERMAI - Najwa Alyani; Tiara Okta Yanti; Bio Chepy Auly; Rosi L. Vini Siregar (TRIBUTE: JOURNAL OF COMMUNITY SERVICES, 2025)
Waste management remains a challenge in various regions, including urban areas such as Rawa Makmur Permai Village, Bengkulu City. Low public awareness of waste sorting at home is one of the reasons why community-based waste management is less than optimal. To address this issue, this community service activity aimed to increase community understanding and participation through outreach on the waste bank initiative in RW 03. The implementation method included preparation, implementation, and evaluation. The activity was conducted in a participatory and educational manner, featuring speakers from the Environmental Agency and local waste bank managers. Evaluation was conducted through a questionnaire with participants to gauge understanding and interest in the program. Results showed that 90% of participants understood the material presented and expressed a willingness to participate in waste management in their neighborhood. These findings demonstrate that an appropriate outreach approach can be an effective first step in building environmental awareness and encouraging the establishment of community-based waste banks at the RW level.